The Grammar of the Fall - Kazarinova, Ksenija (Semiotika, 2017)
The aim of this analysis is to show the way of sin formation in one’s mind. As illustration for it, the biblical text is chosen. The story of original sin is quite short, but mysterious. How does it happen that Adam and Eve choose evil instead of God? Are they thrown into the sin or construct it by their selves?Using the semiotics of passions the author of the article tries to show the mechanism of transformation of the subject’s conscious-ness. The doubt about God makes subject to choose another axio-logical system. What is more, he is trying to become god himself. The formation of sin goes through the main phases: communica-tion with the tempter and interest → the doubt about God → eu-phoric visions of the future → rebellion against God → rebellious action.The consequences of sin are painful and not such euphoric as it seemed before. The person loses the harmony with everything in the world, he can only feel his own nakedness and vulnerability. However, notwithstanding human betrayal, God makes everything to save the mankind.
Keywords: Bible; semiotics; semiotics of passions; sin; temptation